Наближення класів HΩp періодичних функцій багатьох змінних у просторі Lp - Дерев’янко, Н.В. (Український математичний журнал, 2014)
Получены оценки сверху приближения классов HΩp периодических функций многих переменных полиномами, построенными по системе, являющейся тензорным произведением систем функций от одной переменной. С по мощью этого результата установлены точные по порядку оценки ортопроекционных поперечников классов HΩp в пространстве Lp при p∈{1,∞}. We establish upper estimates for the approximation of the classes HΩp of periodic functions of many variables by polynomials constructed by using the system obtained as the tensor product of the systems of functions of one variable. These results are then used to establish the exact-order estimates of the orthoprojective widths for the classes HΩp in the space Lp with p∈{1,∞}.